Biology - Mader, Sylvia S. (McGraw-Hill, 2010)
Biology is a comprehensive introductory biology textbook for non-majors or mixed-majors courses that covers biology in a traditional order from the structure and function of the cell to the organization of the biosphere. The book, which centers on the evolution and diversity of organisms, is appropriate for a one- or two-semester course.